Implementasi Sistem Penunjang Keputusan untuk Menentukan Trayek Terbaik Shuttle Daytrans Menggunakan Metode Weighted Product (WP) Berbasis Web - Rafi Adli Rudianto; Khaerul Ma'mur (Repeater : Publikasi Teknik Informatika dan Jaringan, 2025)
The development of information technology has accelerated digitization in various sectors, including in the decision-making process. In the DayTrans Shuttle service, the selection of the best route is still done manually using Microsoft Excel. This process is time-consuming, inefficient, and has the potential to cause errors and subjectivity. The purpose of this study is to design and develop a web-based decision support system by applying the Weighted Product (WP) method to determine the most optimal shuttle route objectively and efficiently. The research data was obtained through interviews, observations, and literature studies, then analyzed according to system requirements. The development was carried out through the stages of requirements analysis, database and interface design, implementation, and testing. The developed system is equipped with features for managing criteria data, alternative routes, weight calculations, and real-time presentation of recommendation results. The research results show that the system functions well, is able to speed up the route selection process, and produces accurate and transparent recommendations. Thus, this system is expected to improve DayTrans' operational efficiency while supporting the quality of inter-city transportation services.